2020
DOI: 10.1111/eva.13156
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term urbanization impacts the eastern golden frog (Pelophylax plancyi) in Shanghai City: Demographic history, genetic structure, and implications for amphibian conservation in intensively urbanizing environments

Abstract: Understanding the mechanisms of how urbanization influences the evolution of native species is vital for urban wildlife ecology and conservation in the Anthropocene. With thousands of years of agriculture‐dominated historical urbanization followed by 40 years of intensive and rapid urbanization, Shanghai provides an ideal environment to study how the two‐stage urbanization process influences the evolution of indigenous wildlife, especially of anuran species. Therefore, in this study, we used mitochondrial Cyt‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 137 publications
(208 reference statements)
0
12
0
Order By: Relevance
“…Wei et al. (2021) examined the impact of long‐term urbanisation on the Eastern golden frog ( Pelophylax plancyi ) in Shanghai, China, and found that contemporary effective population sizes ( N e ) and genetic diversity remained comparable between urban, suburban and rural areas. Moreover, they detected that all populations experienced historical bottlenecks during low‐level urbanisation dominated by agriculture, 700 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al. (2021) examined the impact of long‐term urbanisation on the Eastern golden frog ( Pelophylax plancyi ) in Shanghai, China, and found that contemporary effective population sizes ( N e ) and genetic diversity remained comparable between urban, suburban and rural areas. Moreover, they detected that all populations experienced historical bottlenecks during low‐level urbanisation dominated by agriculture, 700 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…To define the urbanization level of each study site, we obtained landscape data within a 2 km radius of each study site from satellite images of Formosat-2 (June 2012; 2 m resolution) and Google Earth Pro 7.3.2 (Google), and combined aerial photographs with ground surveys to distinguish the land-use types if they were hard to define [39,42]. The land-use types determined included buildings (including commercial buildings, residential buildings, parking lots, and other anthropogenic building sites) and roads (including highways, arterial roads, elevated ring-roads, and other hardened roads) (Figure 1); the percentage of each land-use type in each study site was calculated using ArcMap 10.3 (Environment Systems Research Institute) and Fragstats 4.2 [49] (Table S1).…”
Section: Urbanization Indexmentioning
confidence: 99%
“…Our previous studies indicated that habitat loss and fragmentation caused by urbanization had significant effects on the population dynamics [38][39][40], body size [41], and genetic diversity [42] of frogs in Shanghai, which is the most-urbanized city in China; however, it is less clear whether frogs have altered advertisement calls in response to anthropogenic noise and habitat change caused by urbanization. In this study, we recorded the advertisement calls of two frog species (Fejervarya multistriata and Microhyla fissipes) in 34 study sites along an urban-rural gradient from May to July of 2020 and 2021 in Shanghai, analyzing five characters of advertisement calls: temporal parameters, including CD, CI, CR, and PR; and a spectral parameter, DF.…”
Section: Introductionmentioning
confidence: 99%
“…However, as amphibians are small-bodied animals, they can survive in small patches of forested and humid areas of ‘green spaces’, provided that these areas are not heavily polluted or disturbed ( Hamer and McDonnell, 2008 ). The impact of urbanization on the biodiversity ( Callaghan et al, 2021 ; Yang, L. et al, 2022 ) and genetic structure ( Wei et al, 2021 ) of amphibian populations has been extensively studied, but microbial data records associated with amphibian hosts in urban settings are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Symbiotic microorganisms are critical for amphibian survival ( Becker et al, 2015 ) and adaptation to rapid environmental changes ( Xu et al, 2020b ; Barnes et al, 2021 ). Consequently, it is crucial to elucidate the response of the amphibian symbiotic microbial community to rapid urbanization, which is valuable for wildlife conservation in urban settings ( Wei et al, 2021 ). However, urban ecosystems present distinctive microhabitat and microclimate conditions in comparison to wild regions ( Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%